Quantifying stormwater pollutants and the efficacy of sustainable drainage systems on the R300 highway, Cape Town - Robertson, Abby Jane (Urban Water Management, 2017)
Stormwater provides a direct link between urban infrastructure and the urbanised natural environment. In particular, highway drainage presents a high risk of pollution when compared to other urban land use areas (Ellis et al., 2012); introducing heavy metals, suspended solids and hydrocarbons to urban waterways. This research investigated runoff from the R300 highway, located in the greater Cape Town area. The City of Cape Town Management of Urban Stormwater Impacts Policy requires the treatment and attenuation of stormwater from developments within the city, and proposes Sustainable Drainage Systems (SuDS) as a means to achieve this (CSRM, 2009b). SuDS are structural and process controls that attenuate surface drainage, improve runoff water quality, provide amenity and deliver ecosystem services. This study characterized the R300 runoff through a sampling program and modelling exercise in order to provide an indication of the ability of SuDS to manage highway runoff in South Africa. Sediment and runoff samples were collected from the road surface and an undeveloped parcel of land adjacent to the highway. The sampling results showed that heavy metals, suspended solids and phosphorus are present in significantly greater concentrations in road runoff compared to rainwater from the same area. The concentration of aluminium, copper, lead, zinc and phosphorus exceed the Department of Water and Sanitation's water quality guidelines for aquatic ecosystems in excess of 1000%. The concentration of heavy metals, phosphorus and fats, oils and greases was significantly greater in road sediment compared to sediment from the surrounding area. Barring copper, all contaminant concentrations in the road surface sediment are less than the maximum concentration required to protect ecosystem health. The R300 rainfall-runoff response was modelled in PCSWMM to evaluate the performance of SuDS such as infiltration trenches, bioretention areas and swales for managing highway runoff in terms of quantity and quality. The modelling exercise showed SuDS to be a viable means to attain the City of Cape Town's stormwater objectives, provided that SuDS are implemented in treatment trains along the entire road length.